Oligarki dalam Demokrasi serta Prakteknya dalam Politik Hukum Indonesia - Konstantinus Budi (Syntax Corporation Indonesia, 2024)
Oligarchy, or political domination by a small number of individuals or groups, has become a concern in the context of democracy. The existence and practices of oligarchy can have significant implications for the formation of legal policy and the distribution of justice. The aim of this research is to investigate the concept of oligarchy in democracy, as well as analyze how oligarchy is practiced in Indonesian legal politics. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the concept of oligarchy in democracy refers to a political system in which political power is concentrated in the hands of a small group of individuals, often having close relationships with certain politicians and supporters. Oligarchy management in Indonesian legal politics is carried out through oligarchic political practices carried out by an elite group consisting of politicians, businessmen and military figures who hold power. This oligarchic political practice does not occur without reason, because indirectly, several legal provisions in Indonesia actually extend political domination that should be democratic. This situation makes it difficult to avoid oligarchic politics in Indonesia.